2017
DOI: 10.1021/acs.nanolett.6b03795
|View full text |Cite
|
Sign up to set email alerts
|

InxGa1–xP Nanowire Growth Dynamics Strongly Affected by Doping Using Diethylzinc

Abstract: Semiconductor nanowires are versatile building blocks for optoelectronic devices, in part because nanowires offer an increased freedom in material design due to relaxed constraints on lattice matching during the epitaxial growth. This enables the growth of ternary alloy nanowires in which the bandgap is tunable over a large energy range, desirable for optoelectronic devices. However, little is known about the effects of doping in the ternary nanowire materials, a prerequisite for applications. Here we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 40 publications
4
50
0
Order By: Relevance
“…Looking next at the inverse GaInP:Zn/InP:S configuration ( Fig. 3(b)), the peak current varies NWs [29,37]. As for the n-InP segments in the four configurations, S doping induced predominately wurtzite (WZ) structure, in line with previous investigation on InP NWs [38].…”
Section: Processing and Measurementssupporting
confidence: 86%
See 2 more Smart Citations
“…Looking next at the inverse GaInP:Zn/InP:S configuration ( Fig. 3(b)), the peak current varies NWs [29,37]. As for the n-InP segments in the four configurations, S doping induced predominately wurtzite (WZ) structure, in line with previous investigation on InP NWs [38].…”
Section: Processing and Measurementssupporting
confidence: 86%
“…Samples were grown in a low-pressure (100 mbar) The total NW length was 2 µm with each segment of 1 µm, mimicking the position of the tunnel diode in a proposed tandem solar cell structure. The NW length was continuously monitored and controlled in situ by use of reflectance spectroscopy [29,30]. To improve pattern preservation, a pre-anneal nucleation of InP was implemented at 280 °C for 1 min at TMIn and PH3 molar fractions of χTMIn = 8.9 × 10 -5 , and χPH3= 6.92 × 10 -3 [25].…”
Section: Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Before growth of the first contact segment, the growth was initiated with an approximately 0.15 µm long InP stub with trimethylindium (TMIn), and phosphine (PH3), at molar fractions of χTMIn= 8.9 × 10 -5 , χPH3 = 6.9 × 10 -3 ( Fig. 1a) [14]. Thereafter, both contact segments and the middle segment were grown using the precursors of TMIn, trimethylgallium (TMGa) and PH3, at molar fractions of χTMIn= 2.7 × 10 -5 , χTMGa= 1.36 × 10 -3 , and χPH3= 5.4 × 10 -3 .…”
Section: Methodsmentioning
confidence: 99%
“…a planar Si cell. The principle of a nanowire tandem cell has been first demonstrated by Heurlin et al 198 200 , while a radial tunnel junctions has recently been demonstrated by Tizno et al 201 . Although a multi-junction nanowire solar cell has not yet been realized experimentally, we like to emphasize that semiconductors with different lattice constant can be stacked into a single nanowire.…”
Section: Economics Of Nanowire Solar Cellsmentioning
confidence: 99%